Age-dependent immune responses in COVID-19-mediated liver injury: focus on cytokines - Aghamohamadi, Nazanin; Shahba, Faezeh; Zarezadeh Mehrabadi, Ali; Khorramdelazad, Hossein; Karimi, Milad; Falak, Reza; Emameh, Reza Zolfaghari (Frontiers in Endocrinology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is potentially pathogenic and causes severe symptoms; in addition to respiratory syndromes, patients might experience other severe conditions such as digestive complications and liver complications injury. The abnormality in the liver is manifested by hepatobiliary dysfunction and enzymatic elevation, which is associated with morbidity and mortality. The direct cytopathic effect, immune dysfunction, cytokine storm, and adverse effects of therapeutic regimens have a crucial role in the severity of liver injury. According to aging and immune system alterations, cytokine patterns may also change in the elderly. Moreover, hyperproduction of cytokines in the inflammatory response to SARS-CoV-2 can lead to multi-organ dysfunction. The mortality rate in elderly patients, particularly those with other comorbidities, is also higher than in adults. Although the pathogenic effect of SARS-CoV-2 on the liver has been widely studied, the effect of age and immune-mediated responses at different ages remain unclear. This review discusses the association between immune system responses in coronavirus disease 2019 (COVID-19) patients of different ages and liver injury, focusing on cytokine alterations.